Vaccinating women previously treated for human papillomavirus-related cervical precancerous lesions is highly cost-effective in China - Zou, Maosheng; Liu, Hanting; Liu, Huan; Wang, Mengjie; Zou, Zhuoru; Zhang, Lei (Frontiers in Immunology, 2023)
Background The 2021 Chinese Expert Consensus on the Clinical Application of the Human Papillomavirus (HPV) Vaccine recommended vaccination for women who previously received ablative or excisional treatment for high-grade squamous intraepithelial lesion (HSIL). This study evaluates the cost-effectiveness of HPV vaccination in women previously treated for cervical precancerous lesions. Methods We used a Markov model to simulate the disease progression of both low- and high-risk HPV subtypes. We followed a cohort of 100,000 women aged 18-45 years who received treatment for cervical precancerous lesions for a lifetime (80 years). We used the Incremental Cost-Effectiveness Ratios (ICER) with a 5% discount rate to measure the cost-effectiveness of nine vaccination strategies, including a combination of HPV bivalent (HPV-2), quadrivalent (HPV-4) and nonavalent vaccine (HPV-9), each with three vaccination doses (one-, two- and three-dose). We conducted one-way sensitivity analysis and probabilistic sensitivity analysis. We followed the CHEERS 2022 guidelines. Results Compared to the status quo, the nine vaccination strategies would result in 3.057-33.124 million incremental cost and 94-1,211 incremental quality-adjusted life-years (QALYs) in 100,000 women previously treated for cervical precancerous lesions. Three vaccination strategies were identified on the cost-effectiveness frontier. In particular, ICER for one-dose HPV-4 vaccination was US10,025/QALY compared to the status quo (no vaccination); ICER for two-dose HPV-4 vaccination was US17,641//QALY gained compared to one-dose HPV-4 vaccination; ICER for three-dose HPV-4 vaccination was US27,785/QALY gained compared with two-dose HPV-4 vaccination. With a willingness-to-pay of three times gross domestic product per capita (US37655), three-dose HPV-4 vaccination was the most cost-effective vaccination strategy compared with the lower-cost non-dominated strategy on the cost-effectiveness frontier. A probabilistic sensitivity analysis confirmed a 99.1% probability of being cost-effective. If the cost of the HPV-9 is reduced to 50% of the current price, three-dose HPV-9 vaccination would become the most cost-effective strategy. Discussion Three-dose HPV-4 vaccination is the most cost-effective vaccination strategy for women treated for precancerous cervical lesions in the Chinese setting.